Expression of Neutral Endopeptidase, Endothelin-1, and Nuclear Factor Kappa B in Prostate Cancer: Interrelations and Associations with Prostate-Specific Antigen Recurrence after Radical Prostatectomy - Panagiotis J. Vlachostergios; Foteini Karasavvidou; Grigorios Kakkas; George Moutzouris; Anna Patrikidou; Ioannis A. Voutsadakis; Danai D. Daliani; Elias Zintzaras; Michael D. Melekos; Christos N. Papandreou (Prostate Cancer)
Objective. To study the impact of the neutral endopeptidase (NEP)/neuropeptides (NPs) axis and nuclear factor kappa B (NFκB) as predictors of prostate-specific antigen (PSA) recurrence after radical prostatectomy (RP). Patients and Methods. 70 patients with early-stage PC were treated with RP and their tumor samples were evaluated for expression of NEP, endothelin-1 (ET-1) and NFκB (p65). Time to PSA recurrence was correlated with the examined parameters and combined with preoperative PSA level, Gleason score, pathological TNM (pT) stage, and surgical margin (SM) assessment. Results and Limitations. Membranous expression of NEP (P<0.001), cytoplasmic ET-1 (P=0.002), and cytoplasmic NFκB (P<0.001) were correlated with time to PSA relapse. NEP was associated with ET-1 (P<0.001) and NFκB (P<0.001). ET-1 was also correlated with NFκB (P<0.001). NEP expression (P=0.017), pT stage (P=0.013), and SMs (P=0.036) were independent predictors of time to PSA recurrence. Conclusions. There seems to be a clinical model of NEP/NPs and NFκB pathways interconnection, with their constituents following inverse patterns of expression in accordance with their biological roles and molecular interrelations.